Penjadwalan Service Kendaraan Motor Dengan Metode Rapid Application Development dan Algoritma First in First out (FIFO) Berbasis Mobile - Akbar Mulia Ardiansyah; Septi Andryana; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
In the competitive business world, new companies emerge and each company strives to improve the quality of customer service to maintain their business. However, in motorbike workshops today, services are still manually performed by one mechanic for one customer, taking a considerable amount of time. This can lead to customer dissatisfaction if there are queue jumpers, causing customers to cancel the desired services. To enhance the quality of the company, it is important to leverage technological advancements, develop new systems, and provide accurate information. This research utilizes the Rapid Application Development (RAD) method and the First In First Out (FIFO) algorithm to develop an application rapidly through iterative and repetitive feedback processes. The application is designed to meet the needs of users, features, and necessary workflows. Application testing is conducted to ensure the proper functioning of the designed and implemented features. The results of the design and testing indicate that this application can facilitate motorbike workshops in developing scheduling systems for motor vehicle services. Consequently, the use of RAD and FIFO algorithm in this application's development is expected to enhance efficiency and service quality in motorbike workshops, while providing convenience in scheduling vehicle services for customers